EMPLOYING THE STYLES OF POP ART IN THE ADVERTISING POSTER - Zahraa Abdel Kareem Ibrahim, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The major European and American role was prominent in defining the characteristics that art was interested in, the most important of which was the popular art that appeared at the end of the twentieth century, which was characterized by many data on all social, political, and economic levels. Pop art had a direct and noticeable reflection on all design arts. The current research is concerned with the most important methods and their artistic and technical implications in the poster for my advertisement and is summarized in several chapters. The first chapter is concerned with mentioning the research problem: What are the effects of popart on the methods and techniques of the advertising poster? The importance of the research is formulated as follows: It benefits students and researchers in the same Specialization is to adopt it as a reference in the field of design in general and advertising design in particular, and the aim of the research was: to identify the most important methods and trends of pop art used in the design of advertising posters, while the second chapter included two topics, the first topic dealt with the concept of pop art, its origin and characteristics. The third chapter was concerned with the procedures that included the methodology of the research in which the researcher adopted the analytical descriptive approach because it is a methodological method based on analysis and discussion. The mind of the recipient is about an endless set of mental implications for interpreting the subject as in all models. The most important conclusions: The color values ??have an expressive, aesthetic and other distinctive artistic value in Pop Art and in the final design achievement, as they have an expressive dimension that mimics the recipient emotionally through their psychological impact.